STUDY ON THE ATHLETIC PREPARATION OF JUNIOR HANDBALL PLAYERS IV (12-13 YEARS) (University Arena, 2024)
Background. Handball is accessible to everyone. It can be practiced by children and young people, men and women and even older people. Most technical procedures are executed by hand, and the ball being small can easily control. In the process of continuous lifting of athletes' capacities, physical and technical training are factors whose weight is special for the successful solving of the objectives and tasks of a certain stage of training. Their judicious ratio and connection depends to a large extent on the level of training an athlete can achieve.Objectives. Studying the methodology for developing specific motor skills through investigations and documentation on the literature, as well as on the training programs used by junior handball players in the training process, in the preparatory stage; The collection of data from the coach's practice on the basis of which, by processing, the characteristics of the methods for developing specific motor qualities will be established; Comparing all these data and studying the existing concordances or discrepancies in the training plans of junior handball players. Based on this, the conclusions of the paper will be drawn up to improve the methodology for the development of motor skills in the preparatory phase.Study hypothesis. If a systematization of the means and methods of developing the motor skills specific to athletics is achieved in the preparatory stage, of the training programmes, then we will be able to contribute to a better athletic training of junior handball players IV.Methods. The research methods used in this study were: The bibliographical study method; The Observation method; The Testing method; The Statistical and mathematical method; The Graphic method.Conclusion. At the final time of the study, the experimental group achieved better results than the control group in all tests carried out. In this study it was observed that by systematizing the means and methods of development of the motor qualities specific to athletics in the preparatory stage, the training programs, improved the preparation of junior handball players.